THEORETICAL BASIS OF TEACHING LITERATURE IN THE CONDITIONS OF INCLUSIVE EDUCATION AND ITS ROLE IN FORMING THE SOCIO-CULTURAL WORLDVIEW OF STUDENTS - Mamlakat Xudayarovna Latipova (Bright Mind Publishing, 2025)
The article discusses the organization of literature teaching to students of higher education institutions based on a communicative approach in the context of inclusive education in accordance with the methodological approaches of organizational-technological, diagnostic-result blocks based on the conceptual methodological system model, the idea of developing an inclusive process in education and its implementation, determining an individual educational trajectory for students with special needs, and the formation of a socio-cultural worldview of students with limited access to inclusive education.
Keywords: Inclusive education, communicative approach, organizational-technological, educational trajectory, quality and effectiveness of education, development of an inclusive process, general didactic principle, pedagogical competence, and socio-cultural worldview in inclusive education, pedagogical conditions.